The acute effect of jump rope and plyometric jump training on explosive power in swimmers - Ab Kahar, Haris Rafiuddin; Linoby, Adam; Sazali, Razif; Md Yusoff, Yusandra; Haziq, Amrun; Adnan, Aizzat; Zulqarnain, Muhammad (Universiti Teknologi MARA, Negeri Sembilan, 2025)
This study utilizes a crossover research design to investigate the acute effects of plyometric jump training versus jump rope exercises on the explosive power of thirty elite swimmers. By assessing vertical and standing broad jumps before and after the interventions, the research evaluates how these land-based training protocols impact the biomechanical requirements and muscle coordination essential for swimming performance. The findings aim to identify effective supplemental training regimens to enhance the explosive capabilities of competitive swimmers.